'Guess who'? An Italian multicentric study on pigmentation traits prevalence in endometriosis localizations. (July 2022) - Salmeri, N.; Ottolina, J.; Bartiromo, L.; Schimberni, M.; Dolci, C.; Ferrari, S.; Villanacci, R.; Arena, S.; Berlanda, N.; Buggio, L.; Di Cello, A.; Fuggetta, E.; et al.
Highlights: Pigmentary traits have been associated with endometriosis. Certain somatic phenotypes may predispose to specific disease's localizations. Endometriosis has a genetic component. Genetic makeup of somatic traits may provide new inroads in disease's pathogenesis. Abstract: Objectives: Previous evidence seems to support the more common presence of certain pigmentation types in women with endometriosis. The aim of this study was to assess the association of certain somatic phenotypes with specific localizations of the disease. The genetic makeup of those somatic traits may will help in better define the disease pathogenesis. Study design: Multicentric, retrospective study of women aged 18 to 45 with histologically confirmed endometriosis. 575 patients were recruited at eleven different Italian endometriosis clinics from March 2015 to January 2021. Data regarding clinical and surgical features were recorded following the self-administered endometriosis patient questionnaire and the surgical standard of reports approved by the World Endometriosis Research Foundation (WERF). Pigmentation types/somatic phenotypes frequencies among endometriosis localizations were reported. A logistic regression analysis was performed to determine somatic types independently associated with disease' localizations. Results: Having green eyes increased by ∼4 folds (OR 3.7; 95% CI: 1.42–9.61; p  = 0.007) the risk of having a ureteral nodule, whereas brown/black eyes decreased this risk (OR 0.34; 95% CI: 0.13–0.87; p  = 0.025). Consistently, the combination of green eyes and blonde/light brown hairs increased the odds of ureteral endometriosis by more than 5 folds (OR 5.40; 95%CI: 2.02–14.49; p  = 0.001), even after correction for anthropometric confounders (aOR 5.85; 95% CI: 2.13–16.09; p  < 0.001). Conclusions: The association between endometriosis and pigmentary traits has been herein confirmed, with the novel finding of the possible predisposition of ureteral endometriosis in patients with green eyes and blonde/light brown hairs. Further investigation on the genetic makeup of somatic traits may provide new inroads also into the molecular aspects of endometriosis leading to a better understanding of this complex disease.